Two-body hidden charm decays of D wave charmonia - Xiao-Yu Qi; Qi Wu; Xing-Dao Guo; Dian-Yong Chen (European Physical Journal C: Particles and Fields)
Abstract The experimental observations of $$\psi _2(3823)$$ ψ 2 ( 3823 ) and $$\psi _3(3842)$$ ψ 3 ( 3842 ) make D wave charmonia family abundant. In the present work, we investigate the hidden charm decay processes of spin triplets of the D-wave charmonia with the meson loop mechanism. The model parameter $$\alpha _\Lambda $$ α Λ is determined by reproducing the branching fraction of $$\psi (3770)\rightarrow J/\psi \eta $$ ψ ( 3770 ) → J / ψ η . With this range of model parameter values, the branching fractions (partial widths) of $$\psi (3770) \rightarrow \eta _c \omega $$ ψ ( 3770 ) → η c ω , $$\psi _2(3823)/\psi _3(3842) \rightarrow J/\psi \eta $$ ψ 2 ( 3823 ) / ψ 3 ( 3842 ) → J / ψ η , $$\psi _2(3823)/\psi _3(3842) \rightarrow \eta _c \omega $$ ψ 2 ( 3823 ) / ψ 3 ( 3842 ) → η c ω are estimated. Our estimations find that the partial width of $$\psi _2(3823) \rightarrow J/\psi \eta $$ ψ 2 ( 3823 ) → J / ψ η is $$\left( 29.64^{+4.01}_{-4.63}\right) \ \textrm{keV}$$ 29 . 64 - 4.63 + 4.01 keV , and the partial width ratio of $$\psi _2(3823) \rightarrow J/\psi \eta $$ ψ 2 ( 3823 ) → J / ψ η relative to $$\psi _2(3823)\rightarrow \gamma \chi _{c1}$$ ψ 2 ( 3823 ) → γ χ c 1 is about $$10\%$$ 10 % , which could be tested by further precise measurements from the BESIII, Belle II and LHCb Collaborations.